2021
DOI: 10.1016/j.omto.2021.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EGFR sensitizes 5-Fu-resistant colon cancer cells through modification of the lncRNA-FGD5-AS1-miR-330-3p-Hexokinase 2 axis

Abstract: 5-Fluorouracil (5-Fu) is a widely applied anti-cancer agent against colorectal cancer (CRC), yet a number of CRC patients have developed resistance to 5-Fu-based chemotherapy. The epidermal growth factor receptor (EGFR) is recognized as an oncogene that promotes diverse cancer progresses. In addition, long noncoding RNAs (lncRNAs) are essential regulators of cancers. Here we report that EGFR and lncRNA-FGD5-AS1 promoted 5-Fu resistance of CRC. By establishing the 5-Fu-resistant CRC cell line, we detected that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Saptinib, an EFGR inhibitor, could increase 3H‐PTX accumulation in tumor cells and reverse MDR in SW720/Ad300 cells through stimulating ATPase which competitively inhibits 3H‐PTX uptake 99 . Erlotinib, a specific inhibitor of EGFR, could effectively strengthen the antitumor effect of 5‐FU via modulating the EGFR‐FGD5‐AS1‐miR‐330‐3p‐hexokinase 2 (HK2) pathway 100 …”
Section: Protein Inhibitorsmentioning
confidence: 99%
“…Saptinib, an EFGR inhibitor, could increase 3H‐PTX accumulation in tumor cells and reverse MDR in SW720/Ad300 cells through stimulating ATPase which competitively inhibits 3H‐PTX uptake 99 . Erlotinib, a specific inhibitor of EGFR, could effectively strengthen the antitumor effect of 5‐FU via modulating the EGFR‐FGD5‐AS1‐miR‐330‐3p‐hexokinase 2 (HK2) pathway 100 …”
Section: Protein Inhibitorsmentioning
confidence: 99%
“…Other studies found that miR-330-3p levels were reduced in CRC tissues (see Table 10 ) compared to adjacent normal tissues in patients, suggesting that miR-330-3p may act as a tumor suppressor (Xu et al 2017 ). Importantly, miR-330-3p levels were also decreased in 5FU-resistant CRC tissues compared to 5FU-sensitive CRC tissues after surgery (Gao et al 2021a ). Moreover, it was shown that ectopic expression of miR-330 mimics directly decreased the level of TYMS -encoded protein and increased the sensitivity of CRC cells to the cytotoxic effect of 5FU (Xu et al 2017 ).…”
Section: Mirnas Targeting Tyms Mrnamentioning
confidence: 99%
“…Although miR-330-3p can target a variety of tumor suppressor genes, including PTEN and PDCD4 , and is therefore up-regulated in various cancer types (see Table 11 ). In CRCs, however, miR-330-3p is down-regulated and targets TYMS mRNA and HK2 mRNA (Gao et al 2021a ). HK2 encodes Hexokinase 2 catalyzing the rate-limiting step of glucose metabolism and is therefore an enzyme that is highly expressed in rapidly growing cancer cells (Pedersen 2007 ; Sun et al 2018b ).…”
Section: Mirnas Targeting Tyms Mrnamentioning
confidence: 99%
“…( 60 ) have reported that lncSLCC1 was upregulated in CRC and promoted glycolysis by transcriptionally activating HK2 ( 60 ). Another well documented lncRNA interacting with HK2 is lncRNA FGD5-AS1, which has been illustrated to promote glycolysis through the miR-330-3p-HK2 signaling network ( 67 ). Moreover, a lncRNA DANCR-miR-125b-5p-HK2 axis has been well established in colon cancer cells, which can promote aerobic glycolysis ( 75 ).…”
Section: Regulation Of Glucose Metabolic Reprogramming By Lncrnasmentioning
confidence: 99%
“…LncRNA HCG11 has been validated to facilitate 5-FU resistance by sponging miR-144-3p and upregulating PDK4 in CRC ( 64 ). Similar to HCG11, lncRNA FGD5-AS1 promotes glycolysis and 5-FU resistance of CRC cells by acting as a ceRNA for miR-330-3p ( 67 ). Besides, lncRNA UCA1 is documented to contribute to paclitaxel (Taxol)-resistance and promote glycolysis by facilitating the expression of HK2 and LDHA in CRC ( 59 ).…”
Section: Regulation Of Glucose Metabolic Reprogramming By Lncrnasmentioning
confidence: 99%